2019
DOI: 10.1145/3303704
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Authenticated Key Agreement Protocol With Dynamic Credential for WSNs

Abstract: Public key cryptographic primitive (e.g., the famous Diffie-Hellman key agreement, or public key encryption) has recently been used as a standard building block in authenticated key agreement (AKA) constructions for wireless sensor networks (WSNs) to provide perfect forward secrecy (PFS), where the expensive cryptographic operation (i.e., exponentiation calculation) is involved. However, realizing such complex computation on resource-constrained wireless sensors is inefficient and even impossible on some devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Security Functionality Comparisons. Table 3 summarizes the comparison of the functionality features of the recent user authentication protocols [1,8,33,45,50,60]. It can be observed that the proposed protocol offers improved security and functionality features, in comparison to the other recent protocols.…”
Section: Comparative Studymentioning
confidence: 99%
See 3 more Smart Citations
“…Security Functionality Comparisons. Table 3 summarizes the comparison of the functionality features of the recent user authentication protocols [1,8,33,45,50,60]. It can be observed that the proposed protocol offers improved security and functionality features, in comparison to the other recent protocols.…”
Section: Comparative Studymentioning
confidence: 99%
“…In this section, we compare our proposed protocol in terms of computation overhead with those of recent related protocols [1,8,33,45,50,60]. The protocol comprises four phases: user and sensor node registration phase, login phase, key agreement and authentication phase, and password and biometrics change phase.…”
Section: Computation Overhead Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…ECC‐based optimal key pre‐distribution and session management schemes are proposed in [1, 2] for maintaining a significant trade‐off between node connectivity, resilience, and storage pre‐requisites. ECC two‐factor user authentication protocols for secure communications in ad hoc wireless sensor networks (WSNs) are proposed in [3, 4], which counter node impersonation, dictionary, node replay, node compromise, Man‐in‐the‐middle (MITM), and stolen‐verifier attacks, while maintaining perfect‐forward‐secrecy. The review further analyses the impact of prominent security threats viz.…”
Section: Literature Reviewmentioning
confidence: 99%